The Value of Spirituality in Keluarga Persilatan Ki Ageng Pandan Alas - Muhammad Hanif (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Pencak silat is cultured in Madiun and pencak silat has become an icon of the Madiun Regency government as "Kampung Pesilat" and Madiun City as "Kampung Pendekar". Excessive thing happening among pencak silat organizations is a primodialism conflict. However, there are several pencak silat (martial arts) organizations that have never been involved in conflict, one of which is Keluarga Persilatan Ki Ageng Pandan Alas. This organization is able to make its members behave and act according to norms. Of course, there is a spiritual value, but not many people know about it. For this reason, it is interesting in having the research with the aim of describing and explaining the spiritual value of Keluarga Persilatan Ki Ageng Pandan Alas. This study used a qualitative ethnographic approach. The technique of collecting data was by interviewing, observing, and recording documents. The data obtained were validated using triangulation techniques. Meanwhile, the data analysis used an interactive model. The results show that Keluarga Persilatan Ki Ageng Pandan Alas contains spiritual values. The spiritual value of the organization is manifested in objectives, symbols, organizational activities, and martial arts moves, namely forming people who have faith and devotion to God, have noble character, become saving hands, always do good to the surrounding in order to prepare themselves to face God's call, a death. The values of spirituality become the power, spirit, and life principle, spirit of the organization in relation to oneself, the social and natural environment, and God.